The use of educational and speech situations at the stages of learning the scientific style of speech - Dementieva , T. (New Collegium, 2021)
This article considers the stages of teaching the scientific style of speech of foreign students in pre-university training. Based on the analysis of the scientific literature, it is concluded that the effectiveness of classes in teaching oral language in a foreign language is achieved through the use of communicative and activity approaches, as well as the use of learning and speech situations that will help bring learning closer to natural communication. Therefore, the methodological basis is a threefold approach to learning theory. Given the classification of stages of formation in foreign listeners of full-fledged mental actions, four stages were identified, through which it is necessary to conduct foreign listeners in order to form in them speech skills and abilities within the scientific style of speech. The main task of the first stage (motivational-target) is to direct foreign students to study the scientific style of speech and develop interest in this discipline, mastering which will allow them to participate in communication in the educational and professional sphere and also partially prepare them for professional activity. At the content-preparatory stage, foreign students create guidelines for mental activity, ie there is an acquaintance and consolidation of grammatical constructions of scientific style of speech and the necessary scientific vocabulary, on the basis of which they will be able to perform any speech tasks. At the communicative stage, foreign students participate in communicative activities, forecasting and planning of speech, its production based on the studied grammatical constructions and the necessary scientific vocabulary, using speech etiquette, realization of skills of dialogic and monologue speech using educational speech terminology. At the final analytical-corrective stage the analysis and correction of formation of levels of oral speech of foreign listeners is provided and is realized through independent work on conversational educational and speech situations.